Bioactive landscape and therapeutic potential of Job’s Tears (Coix lachryma-jobi L.) seeds: A comprehensive review of phytochemistry, pharmacology, and industrial applications - Simardeep Kaur; Maharishi Tomar; Karishma Seem; Ayantika Ghosh; Prabha Singh; Sushmitha J; Gurkanwal Kaur; Amit Kumar; Rakesh Bhardwaj; Amritbir Riar (Applied Food Research, 2025)
Coix lachryma-jobi L. (Job’s tears) is an underutilized cereal crop with a diverse array of phytochemicals, making it an ideal candidate for nutraceutical and industrial exploitation. This review comprehensively examines the diverse compositional profile of coix seeds (CS), highlighting key bioactive constituents including phenolic acids, flavonoids, phytosterols, polysaccharides, coixol, and coixenolide, and their extraction and analytical characterization using advanced chromatographic and spectrometrictechniques. These compounds exert multifaceted bioactivities, including antioxidant, anti-inflammatory, lipid-modulatory, antidiabetic, and antineoplastic effects, mediated through critical molecular targets such as Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-κB), Phosphoinositide 3-Kinase / Protein Kinase B, AMP-Activated Protein Kinase (AMPK), and Nrf2. Clinical evidence supporting the therapeutic efficacy of coix-derived formulations, particularly Kanglaite®, highlights its translational relevance. Additionally, emerging industrial applications inclduing gluten-free product development, biomaterials, resistant starch innovation, and cosmeceutical formulations, have also been discused. Despite significant advances, further research is required to elucidate genotype–chemotype relationships, optimize green extraction methodologies, and validate bioefficacy through clinical trials. This review serves as a comprehensive scientific resource for researchers aiming to explore the nutraceutical potential, pharmacological mechanisms, and industrial applications of CS through its bioactive composition, extraction methods, and therapeutic insights.